Experimental activities try as strategy for teaching Physics: Case study in two does Schools public municipality of Santana-AP - Josivaldo Ferreira Gomes; Erveton Pinheiro Pinto; Henrique Duarte da Fonseca Filho (Estação Científica, 2017)
This work, developed in two public schools, both in the city of Santana-AP, suggests through field research, the use of experimental activities by teachers as a strategy to improve the teaching of Physics in basic school. Two questionnaires were applied, with questions about the content worked until the moment, one before and one after the experimental lesson. Analyzing the questionnaires, it was possible to notice that the students obtained better results after the experimental lesson.